It’s Robot Time: The Use of Automated Written Feedback in L2 Writing: A Reflection of Student Engagement - Ahmad Syafi’i; Oikurema Purwati; Ahmad Munir (ELITE Association Indonesia, 2023)
In this paper, we discuss a critical reflection on the extent to which the use of automated written corrective feedback, in this case, Paper Rater, aligned with the actual classroom implementation, particularly viewed from students’ perception and their writing performance. Students perceive that the feedbacks given during the revision process are useful, particularly in teacher feedback, peer, and the Paper Rater. All students generally understand all the comments/corrections they get from their lecturer, and peer. Some students ignore the whole task after reading the peer's feedback. Students are behaviourally engaged with the multiple feedbacks they receive during the revision process. They also believe that the changes they make in the second draft make my writing better. The feedback they received from their lecturer makes them feel willing to do the task again and will overcome their mistakes with practice. Students are happy with the corrective feedback they receive from teacher, peer and Paper Rater. It clarifies that the students are cognitively engaged with the multiple feedbacks they received. The students also claimed that teacher-student conference is very helpful to mediate their confusion. Keywords: Robots, automated written